A SHARED INFORMATION SYSTEM FOR TOURISM ENTERPRISES IN DEVELOPING ECONOMIES - Tyynelä, Lauri Matti (My University, 2011)
In a developing economy's business environment, introduction of new technology creates a large potential for more effective and streamlined production of tourism services. This study shows guidelines of design of an inter-organizational information system for small tourism enterprises. The entrepreneurial goal is to support strategic alliances in order to obtain better market-fit and sustainable competitive advance. This requires that the enterprises are capable of evaluating their existing processes, identify and outline improvements, and implement them. More than that, enterprises have to execute profound strategic changes in their business processes. For this change, study shows that adaption of supportive information system can be a key factor to satisfy these demands. Firstly, using systematic literature review the study identifies global trends of e-tourism. Secondly the trends are compared with the reality of small tourism enterprises in Nicaraguan Caribbean coast. With interview and brain storming sessions with hotel managers and local tourism specialists, desired state of e-tourism enhanced business processes is defined. Performance gaps and solutions are identified and outlined in order to reach new customer segments and better customer satisfaction with use of inter-organizational information system. With help of shared information system, enterprises search for sustainable economic growth and more stable business environment for their activities. The scientific domain of research is Information systems science. The method used for data collection and interpretation is systematic literature review and human and institutional capacity development -method. As result, the research identifies critical business processes when implementing e-Tourism services into tourism enterprises in developing economies. Strategic solutions for sustainable improvements in business processes supported by use of shared information system are outlined. As a practical result, the study lists required steps in order to reach desired changes in tourism enterprises with e-tourism initiative. Specification of requirements for information system is made. The implementation process and construction of information system is left out from this research and it requires later its own case study.
Keywords: e-Tourism; developing economies; shared information systems; design science; HICD; fi=Tietotekniikka (KTM)|en=Computer Science|; fi=Tietotekniikan koulutusohjelma (DI)|